Increased brain volume in the early phase of aneurysmal subarachnoid hemorrhage leads to delayed cerebral ischemia - Sun, Chao; Qin, Bin; Zhang, Jingyu; Liang, Yidan; Cui, Min; Yang, Qiang; Wang, Yanglingxi; Gong, Jian; Xiang, Yi (Frontiers in Surgery, 2024)
ObjectiveTo investigate the correlation between the swelling rate of brain volume within the first 48 h after aneurysmal subarachnoid hemorrhage and the subsequent development of delayed cerebral ischemia.MethodsA retrospective analysis was conducted on patients with spontaneous aneurysmal subarachnoid hemorrhage admitted to the Neurosurgery Intensive Care Unit of the First Affiliated Hospital of Chongqing Medical University between January 2020 and January 2023. The clinical data, treatment outcomes, and imaging data were analyzed. Brain volume was evaluated using 3D-Slicer software at two time points post-hemorrhage: within the first 24 h and between 24 and 48 h. The swelling rate of brain volume was defined as the ratio of the absolute difference between two measurements to the smaller of values. Patients were categorized into two groups based on established diagnostic criteria of delayed cerebral ischemia. Univariate and multivariate logistic regression analyses were performed to identify factors influencing delayed cerebral ischemia.ResultsA total of 140 patients were enrolled in this study. 46 patients experienced delayed cerebral ischemia after bleeding. The swelling rate of brain volume was larger in the DCI group (10.66 ± 8.45) compared to the non-DCI group (3.59 ± 2.62), which showed a statistically significant difference. Additionally, advanced age, smoking history, history of hypertension, loss of consciousness, poor Hunt-Hess grade, high mFisher score, brain volume within 24 h, and IVH were also statistically different between the two groups. Multivariate logistic regression analysis revealed that the swelling rate of brain volume was an independent risk factor for DCI with adjusting the advanced age, smoking history, history of hypertension, poor Hunt-Hess grade, high mFisher score, brain volume within 24 h, and IVH.ConclusionBrain volume significantly increased in patients with aneurysmal subarachnoid hemorrhage during the early phase (within 48 h post-onset). The larger swelling rate of brain volume is an independent risk factor for the development of delayed cerebral ischemia, and it may hold significant predictive value for the incidence of delayed cerebral ischemia.